Design of Single-Phase Induction Motor Soft Starter with Closed Loop Method Using Arduino Microcontroller - Ardhito Primatama; Lutfir Rahman Aliffianto; Ciptian Weried Priananda (Department of Electrical Engineering Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
A closed‑loop soft‑starter for a 220 V/0.5 hp single‑phase induction motor driven by an Arduino micro‑controller and dual feedback (current + speed) is presented. Relative to direct‑on‑line (DOL) starting, the prototype halves the in‑rush current under no‑load conditions (6.62 A versus 3.30 A) and reduces it by 36 % when the motor drives a synchronous generator (8.28 A versus 5.33 A). Starting torque is maintained at ≥ 90 % of the DOL value in both scenarios, whereas transient time rises modestly from 0.77 s to 2.32 s (no‑load) and to 7.92 s under generator load. These findings demonstrate that the proposed soft‑starter mitigates voltage sag and mechanical stress without compromising torque, making it suitable for small‑enterprise applications where three‑phase supplies are unavailable.